Dan Brown: Morphology of a Bestsellersaurus (ENTHYMEMA, 2015)
Dan Brown’s success finds reasons in multiple factors, social, morphological, cognitive and commercial: the cross-medial restructuring of aesthetic communication on a global scale; the use of zero-sum homeostatic mechanisms in shaping themes, characters and meanings; the mixing of history and fiction; the disappearance of naturalistic elements; the time structuring of plots in «packs», cognitively easy to comprehend; the presence of urban settings, recognizable and meaningful for the global tourist; the elimination of ambiguous elements, favouring an aesthetic orientation to problem solving.
Keywords: fake; metalepsis; augmented reality; emplotment; oxymoron; immersivity